CALCULATE THE VALUES OF SOME PHYSICAL PROPERTIES OF Se0.3Te0.7 ALLOY PREPARED AT DIFFERENT SUBSTRATE TEMPERATURES - Saeed, Nada M (Al-Nahrain Journal of Science, 2009)
In this paper; Se0.3Te0.7 alloy was prepared by mixing Selenium and tellurium of high purity using vacuum evaporation technique, this alloy was prepared as thin films at different substrate temperature; (25, 50, 100, 150) Co. The annealing was done for some of the prepared films at 200 oC.The powder of the prepared alloy was tested by X-Ray diffraction; the result shows that the structure of the Se0.3Te0.7 alloy was polycrystalline. From Hall effect results; the films was found as p-type, the density of the charge carriers (N) was calculated at different substrate temperature, the concentration of charges carriers of the annealed films was decreased.The optical properties of Se0.3Te0.7 films were studied, the values of the optical energy gaps were calculated and it was 0.48 eV at room temperature, this value was increase at the increasing of the substrate temperature. The value of energy gap of the annealed film was calculated and it was 0.62 eV at room temperature.The refraction index was calculated at room temperature as a function of the wave length at 2100 nm; it found to be 4.2.